2016
DOI: 10.1080/00324728.2016.1253857
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and fertility decline: Insights from historical transitions in Europe and North America

Abstract: We have good knowledge of the timing of the historical fertility transitions in different regions, but we know much less regarding specific features and causes. In this study, we used longitudinal micro-level data for five local populations in Europe and North America to study the relationship between socioeconomic status and fertility during the transition. Using the same analytical model and identical class scheme, we examined the development of socioeconomic differences in marital fertility and related it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 62 publications
10
45
1
Order By: Relevance
“…The results obtained in this study are similar to those observed in studies conducted in other countries [15,18,30,31,32,33], despite the disparate methods used to estimate them. Analysis of changes in the patterns of reproductive behaviour during the period of 1995-2014 indicated a similar shift in the age of highest fertility, from 20-24 to 25-29 years, both in rural and urban areas; but in rural areas this process proceeded with several years of delay compare to urban areas.…”
Section: Limitations and Strengthssupporting
confidence: 81%
“…The results obtained in this study are similar to those observed in studies conducted in other countries [15,18,30,31,32,33], despite the disparate methods used to estimate them. Analysis of changes in the patterns of reproductive behaviour during the period of 1995-2014 indicated a similar shift in the age of highest fertility, from 20-24 to 25-29 years, both in rural and urban areas; but in rural areas this process proceeded with several years of delay compare to urban areas.…”
Section: Limitations and Strengthssupporting
confidence: 81%
“…Within countries, countless studies have found associations between demographic outcomes, socioeconomic inequalities, and poverty, with considerably higher risks of poverty often observed among lower‐status groups with large numbers of children and dependents (Westoff and Cross ; Joshi and Schultz ; Banerjee and Duflo ; Ezeh, Mberu, and Emina ; Mberu and Reed ; Canning, Sangeeta, and Yazbeck ; Dribe et al. ). In both cases, demographic variables emerge as closely related to a country's economic potential and its level of domestic inequality—two of the primary explanatory variables typically emphasized in extant literature on global poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The differences can be observable, such as socioeconomic differences in family size (e.g. Dribe et al, 2017), or unobservable, such as differences in attitudes, behaviors or preferences. If these (observable or unobservable) factors also influence the outcomes for the children they will work as confounders of the association between sibship size and the outcomes (for an example, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%